STRENGHTENING THE RURAL ENTREPRENEURSHIP IN THE REPUBLIC OF MACEDONIA - Krstevska, Martina; Trenceva, Nada (International Journal of Economic Practice and Policy, 2017)
The entrepreneurship is seen as a main driving force for the economic development of the Republic of Macedonia in general and particularly for the development of the rural areas. The purpose of this paper is using the survey, statistical method and method of deduction to present the real situation with the rural entrepreneurship in the Republic of Macedonia. The studies in this paper point to conclusion that the rural areas in the Republic of Macedonia are characterized by great abandonment, loneliness, a decade trend of migration and high unattractiveness by the entrepreneurs to conduct business in the rural areas. Based on the survey of the entrepreneurs attitude to start business in rural areas, this paper provide recommendation for outlining future policies, measures and instruments that will facilitate the creation of stimulating sustainable rural entrepreneurship in the Republic of Macedonia.